Linking environmental management and employees' organizational identification: The mediating role of environmental attitude - Hans Jaich (Corporate Social Responsibility and Environmental Management, 2021)
The fundamental research question in the present study is whether perceived environmental management practices relate to employees' organizational identification. Specifically, it is hypothesized that this relationship is mediated by employees' environmental attitudes. The corresponding research model adopts a multi-theoretical approach that combines two different theoretical lenses. Goal-framing theory is introduced to predict whether perceived environmental management practices affect employees' environmental attitudes, while green-person-organization fit is applied to explain the relationship between employees' environmental attitudes and organizational identification. The research model was tested using a cross-sectional research design with data from 206 employees from tourist service companies in Germany. The results, which largely support the research model, shed light on a thus far unexplored mechanism that mediates individual reactions to organizational practices and contrasts the more established proposition that employees first identify with their organization before they develop attitudes that are in accordance with corresponding ingroup norms. Implications for both research and practice are discussed.
Keywords: 650; corporate sustainability; environmental management; goal-framing theory; green-person-organization fit; micro-CSR; organizational identification